Listeria monocytogenes meningitis in elderly patient - Vásquez Alva, Rolando (2020)
Listeria monocytogenes meningitis is a serious and life-threatening disease. It is the third cause of bacterial meningitis, despite being rare. Newborns, elderly, pregnant women and immunocompromised patients are the most affected population. We present the case of a 70-year-old patient with a history of high blood pressure, non-active thyroid cancer, with sporadic food intake outside the home, who is admitted with a 5-day-of-evolution fever syndrome, slight headache and inappetence. On clinical examination, she presented mild to moderate neck stiffness, without significant radiological findings in the central nervous system. She started empirical antibiotic treatment, which was continued for 4 weeks, obtaining both blood culture and cerebrospinal fluid culture positive result for Listeria monocytogenes. The importance of considering this etiology in the diagnosis of meningitis in the adult population is discussed, since an epidemiological change of its virulence towards adult populations could be occurring.